2007
DOI: 10.1128/jvi.00569-07
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Arterivirus Attachment to the Macrophage-Specific Receptor Sialoadhesin Is Dependent on the Sialic Acid-Binding Activity of the N-Terminal Immunoglobulin Domain of Sialoadhesin

Abstract: The sialic acid-binding lectin sialoadhesin (Sn) is a macrophage-restricted receptor for porcine reproductive and respiratory syndrome virus (PRRSV). To investigate the importance of pSn sialic acid-binding activity for PRRSV infection, an R 116 -to-E mutation was introduced in the predicted sialic acid-binding domain of pSn, resulting in a mutant, pSn RE , that could not bind sialic acids. PSn, but not pSn RE , allowed PRRSV binding and internalization. These data show that the sialic acid-binding activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 31 publications
1
72
0
Order By: Relevance
“…PRRSV is then attached and subsequently internalized via clathrin-mediated endocytosis [29] by the macrophage restricted porcine sialoadhesin receptor [44]. Porcine sialoadhesin binds to sialic acids, present on PRRSV viral glycoproteins [14,16]. Following virus internalization, a subsequent pH drop in the endosome is required for virus replication [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRRSV is then attached and subsequently internalized via clathrin-mediated endocytosis [29] by the macrophage restricted porcine sialoadhesin receptor [44]. Porcine sialoadhesin binds to sialic acids, present on PRRSV viral glycoproteins [14,16]. Following virus internalization, a subsequent pH drop in the endosome is required for virus replication [29].…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulphate is not necessary for sialoadhesin to function as a PRRSV internalization receptor, but enhances the interaction of the virus with sialoadhesin. Attachment of PRRSV to sialoadhesin is mediated by sialic acids present on the surface of PRRS virions [14,16]. CD163, a cellular protein in the scavenger receptor cysteine-rich superfamily, has recently been shown also to function as a PRRSV receptor in Marc-145 cells, but its role in PRRSV infection of primary macrophages has not been studied [6].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that pCD163 cooperated with another putative receptor, porcine sialoadhesin (Sn/CD169) (23), to facilitate the PRRSV infection, where the former contributed to the uncoating of PRRSV while the latter promoted the attachment and internalization (invasion) of the virus (40)(41)(42)(43)(44)(45)(46)(47)(48). However, one study showed that Sn gene knockout pigs were infected by PRRSV as usual (49), and a recent study using geneedited pigs demonstrates the indispensability of pCD163 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The N-linked glycans in GP5 were reported to play a role in M/GP5 complex attachment to pig sialoadhesin (pSn) receptor, thus conferring virus tropism to monocyte/macrophage-derived cells (15,42). The attachment was critically dependent on the sialic acid-binding capacity of the pSn receptor as well as on the sialic acids on the viral GP5 glycoprotein (10,11,25,41). Previous studies stated that ablation of a glycan in GP5 reduced or abolished the growth of PRRSV in MARC-145 cells or porcine alveolar macrophages (PAMs) (2,47).…”
mentioning
confidence: 95%